Etnomatematika pada Pakaian Adat Ulos Batak Toba dan Implementasi dalam Rancangan Pembelajaran Matematika - Jawa, Petrus Ignasius Junior; sidabalok, alfrendo; Rudhito, Marcellinus Andy (Universitas Cokroaminoto Palopo, 2024)
The country of Indonesia is rich in culture where there are elements of mathematics in it. One of these cultures is Ulos cloth with various motifs. The results of this study of mathematics in culture can then be implemented in contextual mathematics learning by paying attention to cultural background, which is expected to facilitate and motivate students. The purpose of this research is to explain and expose the existence of ethnomathematics-based learning methods that associate elements of a culture with mathematical learning. With the existence of a culture, every person or individual can know everything that is contained in that culture. By choosing a topic about the cultural diversity of communities in the region of North Sumatra about the customary clothing of Ulos Batak, which in this study explains the existence of ethnomatematics contained in the motifs of the fabric of the Ulos of the Tribe of Batak Toba used in the wedding ceremony. The research method used is descriptive qualitative. The research also reveals how mathematical concepts are reflected in the fabric motifs of the outline, such as transformation, symmetry, and balance. This research uses data analysis techniques i.e. reduction, presentation and drawing conclusions. The data collection technique is carried out with the method of literature study where it is done by searching from various sources about Batak Toba's Modern Clothing then reduced by selecting the necessary information. Research results show that ethnomatematics is present in a variety of fabric motifs, including Passamot, Pengantin, Holong, and Sadum. By understanding the interrelationship between mathematics and culture in the context of the textile fabric, mathematical learning can become more interesting and meaningful for students. The research also emphasizes the importance of understanding and preserving the cultural heritage of the Batak Toba tribe.